In vitro systems toxicology-based assessment of the potential modified risk tobacco product CHTP 1.2 for vascular inflammation- and cytotoxicity-associated mechanisms promoting adhesion of monocytic cells to human coronary arterial endothelial cells. (October 2018) - Poussin, Carine; Laurent, Alexandra; Kondylis, Athanasios; Marescotti, Diego; van der Toorn, Marco; Guedj, Emmanuel; Goedertier, Didier; Acali, Stefano; Pak, Claudius; Dulize, Rémi; Baumer, Karine; Peric, Dariusz; et al.
Abstract: Cigarette smoking causes cardiovascular diseases. Heating tobacco instead of burning it reduces the amount of toxic compounds in the aerosol and may exert a reduced impact on health compared with cigarette smoke. Aqueous extract from the aerosol of a potential modified risk tobacco product, the Carbon Heated Tobacco Product (CHTP) 1.2, was compared in vitro with aqueous extract from the smoke of a 3R4F reference cigarette for its impact on the adhesion of monocytic cells to artery endothelial cells. Human coronary artery endothelial cells (HCAEC) were treated for 4 h with conditioned media from human monocytic Mono Mac 6 (MM6) cells exposed to CHTP1.2 or 3R4F extracts for 2 h or directly with those extracts freshly generated. In vitro monocyte-endothelial cell adhesion was measured concomitantly with inflammatory, oxidative stress, cytotoxicity, and death markers. Furthermore, transcriptomics analyses enabled to quantify the level of perturbation in HCAECs, and provide biological interpretation for the underlying molecular changes following exposure to 3R4F or CHTP1.2 extract. Our systems toxicology study demonstrated that approximately 10–15-fold higher concentrations of the CHTP 1.2 aerosol extract were needed to elicit similar effects as the 3R4F smoke extract on cardiovascular disease-relevant inflammation and cytotoxicity-related mechanisms and markers investigated in vitro . Graphical abstract: Highlights: The development of innovative modified risk tobacco product (MRTP) is necessary for public health concerns. Heating rather than burning tobacco reduced the formation of toxic compound in the aerosol of CHTP 1.2, a potential MRTP. 3R4F reference cigarette smoke extract promotes the adhesion of monocytic cells to HCAECs, a key process in atherogenesis. CHTP1.2 aerosol extract compared with that of 3R4F showed reduced biological impact on vascular pathomechanisms.